(untitled) (Revista Argentina de Cirugía, 2022)
Background: Infected pancreatic necrosis and pseudocyst are complications that, generally, require any type of surgical treatment (laparoscopic, percutaneous or open surgery). Objective: To identify mortality factors in patients who underwent surgery for local complications of acute pancreatitis. Method: It was conducted a literature search in the National Library of Medicine through Pubmed, limited to pub- lications in English since 1990, using the following keywords: pancreatic necrosis, necrosectomy, mortality, morbidity, local complications, surgery and severe acute pancreatitis. In the data base LILACS a similar search was conducted, limited to the Argentine literature, during the period 2000 – 2011. Results: 119 publications were selected and 82 were excluded because of inadequate statistical analysis or insu- fficient number of patients. After the analysis, 37 publications were selected and 6 mortality factors after pancreatic necro- sectomy were identified. These factors were: time between admission and necrosectomy; predominance of liquid or solid components; presence of infection; extension and localization of pancreatic necrosis; presence of organ failure and walled off necrosis. In the search conducted in the LILACS data base, 7 publications about surgery of the local compli- cations of acute pancreatitis were identified. Conclusion: After the literature search, six factors were identified related to the patient evolution after surgery for pancreatic local complications.